BENTUK KOMPONEN NONVERBAL KARYA TARI ELEGI - Purwanta, Eunike Meta; Maryono, Maryono (Greget : Jurnal Kreativitas dan Studi Tari, 2023)
The research on “Bentuk Komponen Nonverbal Karya Tari Elegi” explores the elements contained in dance. This dance is a depiction of a romantic relationship that leads to things that are considered toxic. This paper aims to reveal the meaning of the nonverbal component forms of Elegi dance by interpreting the compound relationships between its elements. Several elements are discussed, namely: theme, movement, facial expressions (polatan), make-up, clothing, floor patterns and music as accompaniment. For problem solving, use verbal and nonverbal concepts from Maryono in the Book Analisa Tari. The research methodology is qualitative with data collection techniques: literature study, observation and interviews. All data that has been collected, classified, processed and analyzed using the triangulation method. The data that has been collected is then compared between one data and other data. This study found that the compound relationship of the nonverbal component elements of the Elegi dance is a dance work presented by two female dancers based on elements of traditional Surakarta style dance which was developed with the theme of romance. The struggle for love that is presented is about a love relationship that failed due to the denial of love and the woman fell into a state of hatred, resentment and anger, but in her downturn a new awareness was born, she got up and moved on to continue living by arranging her entire life so that it was meaningful for herself and others.